Evidence of Gondwana early rifting process recorded by Resende-Ilha Grande Dike Swarm, southern Rio de Janeiro, Brazil. (April 2016) - Guedes, Eliane; Heilbron, Monica; de Morisson Valeriano, Claudio; de Almeida, Julio César Horta; Szatmari, Peter
Abstract: Continental flood basalts and dike swarm have been related to continental breakup process through geological time. The Resende – Ilha Grande Dike swarm (RIGDS) located in the southeast Brazil, is related the Gondwana breakup and composed of dikes/sills intruded in Precambrian gneiss. The dikes have three distinguish orientations: NNW more inland; NS-NNE in the central segment and NE orientation in the coast line, consistent with Precambrian structural lineaments. The swarm comprises high-TiO2 tholeiitic basalts divided into three suites based on REE and Sr and Nd isotope data. The Resende and Volta Redonda suites present higher initial 87 Sr/ 86 Sr ratios between 0.7077 and 0.7065, while Angra dos Reis suite presents values of 0.7066 to 0.7057. Geochemical and isotopic data support the sub-continental lithospheric mantle (SCLM) as the main source for the high-TiO2 basalts. The suites heterogeneities are explained by different compositions of SCLM in accreted Precambrian terranes and/or different degree of partial melting and fractional. 40 Ar/ 39 Ar data indicate age interval between ca. 156 to 144 Ma for the swarm, older than the average for Gondwana breakup (ca. 130-120 Ma). The age interval places the RIGDS between the Karoo magmatism (181-178 Ma) and the Paraná-Etendeka magmatism (133–134 Ma) and indicates that extensional process affected the supercontinent prior the break-up. Graphical abstract: Age comparison between samples from Resende-Ilha Grande dike swarm and other magmatic events related to the Gondwana breakup. 1) Resende-Ilha Grande Dike swarm (this work): Resende suite (VR-ELS-8 and RE–II–22), Volta Redonda suite (NSA-ELS-05), Angra dos Reis suite (VR-ELS-06, VR-ELS-9 and BAN-ELS-10); 2) Santos Basin (Fodor et al., 1983 ); 3) Paraná continental flood (Thiede and Vasconcelos, 2010); 4) PGDS – Ponta Grossa dike swarm (Renne et al., 1996); 5) Campos basin (Misuzaki et al., 1988); 6) SMDS – Serra do Mar dike swarm – high TiO2 Rio de Janeiro (Vieira, 2009); 7) FLDS – Florianopolis Dike swarm (Raposo et al., 1998 ); 8) SMDS – Serra do Mar dike swarm –São Paulo (Regelous, 1993). The error bars represent only values higher than 6 Ma. Map modified from Almeida (1986). Highlights: 40 Ar/ 39 Ar data for Resende-Ilha Grande Tholeiitic Dike Swarm point to early extensional episode ca. 156-144 Ma. The event precedes the onset of Paraná LIP and the Gondwana break-up. Three high-TiO2 magmatic suites identified using geochemistry and Nd and Sr isotopic data. TDM ages suggest basement contamination and are similar to mafic rocks interlayered with Neoproterozoic basement. The swarm represents the precise onshore projection of Pelotas-Santos rift propagator, in the N–S direction.